Career assistance to a team in crisis-transition: An intervention case study in Swedish elite handball - Ekengren, J.; Stambulova, N.; Johnson, U.; Ivarsson, A.; Schinke, R. (Case Studies in Sport and Exercise Psychology, 2020)
In this paper we share how a career assistance program (CAP) was developed, implemented, and evaluated with a Swedish elite handball team. Within this case study the initial version of the CAP`s content was created based on the career-long psychological support services in Swedish handball framework and the first author`s applied experiences. During implementation the head coach terminated unexpectedly and the team appeared in a crisis. This transitional situation led to modification of the CAP to help the players cope with changes. Eighteen players took part in eight workshops dealing with various aspects of their sport and non-sport life (e.g., performance, training, lifestyle, recovery, future planning) with crisis-related issues (e.g., coping with uncertainty) incorporated. Mixed-methods evaluation revealed the players` perceived increase in personal resources (awareness, skills) and decrease in stress and fatigue. Reflections on working in applied sport psychology from a holistic perspective in a dynamic real-life setting are provided.